Macroevolution of sexual size dimorphism and reproduction-related phenotypic traits in lizards of the Chaco Domain - López Juri, Guadalupe (2018)
Comparing sexual size dimorphism (SSD) in the light of the phylogenetic hypothesis may help to understand the phenotypic evolution associated with sexual selection (size of whole body and of reproduction-related body parts). Within a macroevolutionary framework, we evaluated the association between the evolution of SSD and the evolution of reproduction-related phenotypic traits, and whether this association has favored female fecundity, considering also variations according to reproductive modes. We focused on the lizard species that inhabit the Chaco Domain since this is a natural unit with a high diversity of species.